Survival estimates across five life stages of redfin (Perca fluviatilis) exposed to simulated pumped-storage hydropower stressors. Issue 1 (20th April 2022) - Doyle, Katherine E; Ning, Nathan; Silva, Luiz G M; Brambilla, Eduardo M; Deng, Z Daniel; Fu, Tao; Boys, Craig; Robinson, Wayne; du Preez, Jan A; Baumgartner, Lee J
Abstract : Pumped-storage hydropower facilities may facilitate the transfer of redfin ( Perca fluviatilis ) from lower to higher elevation reservoirs and/or among catchments. This would be welcomed in situations where the species is native, but could have detrimental implications for the conservation of native biota where the species is considered a pest. Abstract: The global prevalence of pumped-storage hydropower (PSH) is expected to grow exponentially as countries transition to renewable energy sources. Compared to conventional hydropower, little is currently known regarding PSH impacts on aquatic biota. This study estimated the survival of five life stages (egg, two larval stages, juvenile and adult) of redfin (European) perch ( Perca fluviatilis ) following passage through a PSH facility during the pumping phase. This was achieved by simulating the individual stressors expected to occur during passage through a 2000-MW PSH facility using laboratory-simulated (shear strain and extreme compression) and modelling (blade strike, BS) approaches. Our results indicate that redfin could survive the shear, pressure and BS stressors expected within the PSH facility, but impacts varied among life stages. Juvenile survival was >70% across all shear strain rates, while the survival of eggs and larvae declined markedly as strain rate increased. All life stages had high survival when exposed to rapid compression and BS. The high survival of redfin to the stressors tested suggests the PSH facility could facilitate the passage of redfin during the pumping phase from the lower to the higher elevation reservoir. This outcome would be welcomed in situations where the species is native, but could have adverse implications for the conservation of native biota where the species is considered a pest.